2017
DOI: 10.1515/ssa-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of organic fertilizers on soil organic matter and enzyme activities of soil in forest nursery

Abstract: The aim of the study was to assess the effects of organic fertilization on selected chemical properties of the soil and the activity of dehydrogenase and β-glucosidase in the soil of forest nursery. The main goal was to evaluate the role of organic fertilizers in carbon storage in the forest nursery soil. Sample plots were located in northern Poland in the Polanów Forest District on a forest nursery. Soil samples were collected from horizon 0-20 cm for laboratory analyzes. In soil samples pH, soil texture, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…The organic matter content in the soils treated with AB, FV, and SM increased on average by 14.4%, 16.4%, and 17.6% with each vegetable rotation; TN increased by 17.7%, 22.7%, and 24.0%; AN increased by 16.0%, 19.5%, and 19.1%; TP increased by 65.3%, 67.9%, and 73.7%; AP increased by 39.3%, 41.6%, and 48.4%; TK increased by 9.5%, 12.6%, and 13.3%; AK increased by 20.5%, 34.0%, and 40.6%, respectively. The results highly suggest that the application of mushroom residues and swine manure significantly increased the contents of organic matter and mineral nutrients in the soils, which is consistent with many previous studies [33][34][35][36][37].…”
Section: Effects Of Application Of Mushroom Residues and Swine Manure...supporting
confidence: 92%
“…The organic matter content in the soils treated with AB, FV, and SM increased on average by 14.4%, 16.4%, and 17.6% with each vegetable rotation; TN increased by 17.7%, 22.7%, and 24.0%; AN increased by 16.0%, 19.5%, and 19.1%; TP increased by 65.3%, 67.9%, and 73.7%; AP increased by 39.3%, 41.6%, and 48.4%; TK increased by 9.5%, 12.6%, and 13.3%; AK increased by 20.5%, 34.0%, and 40.6%, respectively. The results highly suggest that the application of mushroom residues and swine manure significantly increased the contents of organic matter and mineral nutrients in the soils, which is consistent with many previous studies [33][34][35][36][37].…”
Section: Effects Of Application Of Mushroom Residues and Swine Manure...supporting
confidence: 92%
“…Further, these authors also found that the replacement of chemical fertilizers with organic manures can increase macro-aggregates, POC, TOC and the yield of crops compared to conventional fertilizers [129]. Organic materials have a positive effect on increasing the SOM (on average 12.9%) compared to the control [130][131][132].…”
Section: Effect Of Organic Fertilizers On Soil Organic Matter and Soi...mentioning
confidence: 91%
“…Pupuk organik mampu meningkatkan ketersediaan hara tanah serta meningkatkan aktivitas mikrobia dalam tanah sehingga mampu menigkatkan kesuburan tanah (Piaszczyk et al, 2017). Hara tersedia yang cukup bagi tanaman menunjang pertumbuhan vegetatif dan pertumbuhan generatif tanaman (Andalasari et al, 2017), sehingga tanaman dapat tumbuh dengan baik dan proses pembungaan lebih cepat.…”
Section: Pendahuluanunclassified